Rural vs Urban Pattern Analysis of Oral Cancer Incidence at Tertiary Care Centre, Rajasthan: An Retrospective Observation Study - Dr. Vipul Choudhary; Dr. Rishi Mangal; Dr. Manish Jain (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Oral cancer is a major public-health problem worldwide, especially in low- and middle-income countries. Significant disparities exist between rural and urban populations due to differences in risk factors, socioeconomic status, awareness, and access to healthcare. Objective: To compare oral cancer incidence, demographic patterns, and associated risk factors between rural and urban populations. Methods: A cross-sectional, retrospective observational study analyzing population-based cancer registry data from 2015–2024. Data included incidence rates, demographic characteristics, stage at diagnosis, and risk-factor prevalence. Results: Rural areas reported a higher oral cancer incidence (29.4/100,000) compared to urban areas (18.6/100,000). Tobacco chewing (52%), areca-nut use (38%), and late-stage presentation (61%) were significantly higher in rural regions. Urban populations had better awareness, earlier diagnosis, and higher screening participation. Conclusion: Oral cancer incidence is substantially higher in rural communities, driven by lifestyle behaviors, limited awareness, and reduced access to healthcare. Targeted prevention, early-detection programs, and infrastructure strengthening are essential to reduce disparities.